PREVALENCE OF FASCIOLOSIS (FASCIOLA HEPATICA LINNAEUS, 1758) IN BOVINE SLAUGHTER COMPANIES IN THE PROVINCE OF IMBABURA, ECUADOR - Cacuango-Quishpe, Jeferson (2021)
Fasciolosis is a zoonosis caused by the parasite Fasciola hepatica Linnaeus, 1758, which, in order to develop its biological cycle, requires an intermediate host (gastropod mollusk, Lymnaeidae), and a definitive host (mammals, including man). This disease has caused annual economic losses of $ 200 M in the world. The objective of the present investigation was; to identify the prevalence of F. hepatica in the bovine slaughter centers, to determine the economic losses, and to identify the agroecological characteristics where the intermediate hosts develop, in the province of Imbabura, Ecuador. A prevalence of F. hepatica of 10,9% was identified, where the Cantón Otavalo presented 190 positive samples (19,7%), being considered the point with the highest prevalence within the study. The positive bovines were 102 males (26,9%) and 277 females (73,1%), which belong to the Mestizo (53,5%), Holstein (42%) and Normando (4,5%) biotype. 78,6% being over two years and 21,4% under two years. There was an annual economic loss of $ 69.547,5 US dollars. The 20 biotopes sampled remained within the average values; distance from the populated center 0,7 kilometers, area of 42,8 m2; 31 mollusks per biotope, soil pH 7,1; water depth 2,3 cm; altitude from 2,019 to 2,772 meters above sea level; temperature of 20 ° C and relative humidity of 74%. The mollusks were located in ditches (55%), puddles (25%), swamps (10%), streams and the ground (5%), with the presence of kikuyo (Pennisetum clandestinum Hochst. Ex Chiov, 1903) and cattails (Schoenoplectus californicus CA Mey., 1850) as dominant species. The province of Imbabura has a moderate prevalence in terms of epidemiology due to fasciolosis, it is confirmed that these areas present an ecosystem suitable for the development of the biological cycle of fasciolosis.